The mental health needs of female inmates in Durban, South Africa - Naidoo, Samantha (My University, 2022)
There is a dearth of literature on the mental health needs of female inmates in lowand middle-income countries, particularly from Africa and South Africa. South Africa has the largest HIV epidemic in the world and has very high rates of violent crime and trauma, including gender-based violence. HIV and trauma have established associations with mental illness. In addition, culture plays an important role in the lives of African people. In light of the above, this study aimed to provide a holistic picture of the mental health needs of female inmates in Durban, South Africa, in a culturally relevant setting. This was achieved through a mixed methods, sequential, explanatory design study which was conducted in two phases. In phase one, the prevalence of mental illness, HIV and trauma was measured among 126 randomly recruited female inmates. This was followed by a qualitative phase which explored the lived experiences of mental illness, trauma and HIV in a diverse cultural setting, among a sub-sample of purposively chosen female inmates from the first phase. Findings revealed a high prevalence of lifetime mental illnesses including major depressive disorder, post-traumatic stress disorder, alcohol and substance use disorders, borderline personality disorder, and suicidal ideation and attempts, as compared to the general population in South Africa, and compared to international incarcerated populations. A significant treatment gap was also inferred from the findings. HIV was very prevalent among female inmates, in keeping with studies of women in the general population in some parts of rural KwaZulu-Natal, however, it was much higher than other inmate populations internationally. The lifetime prevalence of trauma was also elevated. Associations were found between mental illness and trauma, as well as mental illness and HIV. A qualitative exploration of their lived experiences of HIV found that inmates reported feeling supported and accepted in the correctional environment, which contrasted to their experiences of being stigmatised and discriminated against while living in their home communities. Negative community experiences were largely due to the prevalent lack of knowledge and misconceptions. The lived experiences of trauma and mental illness among female inmates highlighted the contribution trauma had on the development of their mental illness and their trajectories into crime. Understanding their cultural backgrounds was crucial in understanding the inmates’ narratives. The mental health needs of female inmates at this correctional centre in Durban, South Africa are concerning and should be considered in the context of their high prevalence of HIV, trauma and cultural backgrounds. Thus, integrated mental health rehabilitation programmes, which are culturally-informed, should be implemented at this correctional centre. Incarceration presents an opportunity to conduct vital rehabilitation, prevention and promotion work in this hard-to-reach and vulnerable population, in order to optimise their mental health and to decrease recidivism. The outcomes can also be transferred to their communities of origin upon release to help curb the epidemics of HIV and gender-based violence in South Africa.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2022